A Focus on Engagement: Defining, Measuring, and Nurturing a Key Pillar of AACSB Standards. (2nd January 2017) - Dostaler, Isabelle; Robinson, Melanie A.; Tomberlin, Thomas J.
ABSTRACT: The 2013 Association to Advance Collegiate Schools of Business (AACSB) Standards emphasize three "pillars" upon which schools accredited by the association must regularly demonstrate quality improvement, namely, impact, innovation, and engagement. Focusing on the last of these, our article examines the concept of engagement through both a content analysis of the 2013 AACSB Standards and an empirical study exploring different types of course-level engagement within an undergraduate business course (measured using the Student Course Engagement Questionnaire; Handelsman, Briggs, Sullivan, & Towler, 2005). The results of our content analysis of the 2013 AACSB Standards underscore the focus placed on engagement within the AACSB documentation. However, it is also noted that the definition of engagement within the AACSB Standards is somewhat vague. The findings of our empirical study ( N = 142) suggest that students were engaged in the course and that three of the four types of engagement measured (skills, participation/interaction, and performance engagement) were positively correlated with final performance in the course.